Transforming Learner Autonomy in Arabic Language Learning Through Artificial Intelligence - Nugrawiyati, Jepri; Nurwendah, Yusti Dwi; Nasrullah, Muhammad; Abidin, Nadiah (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2026)
The development of Artificial Intelligence (AI) in education has transformed the ways in which students learn Arabic, particularly in the context of fostering learner autonomy. This study aims to explore the role of AI as a facilitator of learning autonomy, identify emerging challenges, and examine pedagogical implications for higher education. The methodology employed is an integrative review, synthesizing recent literature on AI, self-regulated learning, and Arabic language acquisition. Findings indicate that AI can enhance learner autonomy through support for multimodal learning experiences, material personalization, and real-time feedback that promotes student reflection and self-regulation. On the other hand, AI also presents risks such as pseudo-autonomy, epistemological errors, and ethical and academic challenges, which necessitate critical digital literacy and pedagogical oversight. Effective AI integration requires instructors to act as facilitators, ethical guides, and quality controllers of learning processes. This paper concludes that AI holds significant potential to strengthen authentic and responsible learner autonomy, provided it is employed within a reflective, critical, and ethical pedagogical framework. These findings offer important implications for the design of technology-based Arabic language instruction and the development of strategies to reinforce learner autonomy among digital-native students